Analisis Swot Dalam Menentukan Strategi Pemasaran Pada Umkm Di Masa Pandemi Covid-19 (Studi Kasus Pada Pentol Pedas Alesha Bumiayu Kota Malang) - Yulia Ifatur Rohma; Eka Farida; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study is: 1) To find out the SWOT analysis and marketing strategy on MSMEs of Pentol Pedas Alesha, 2) To find out the application of SWOT analysis to determine marketing strategies for MSMEs of Pentol Pedas Alesha,3) To find out the marketing strategies applied to MSMEs Pentol Pedas Alesha. The results of the study used SWOT Analysis by identifying internal and external factors, namely the position of strength (Strenght) is greater with the total score obtained by 2.86 compared to the weakness position (Weakness) of 0.60. Then on the external factors of the company the opportunity position (Opportunity) is greater with a score of 2.24 compared to the threat position (Threats) of 0.50. The results of the calculations from the analysis showed that the implementation of the strategy in MSMEs using the Growth Oriented Strategy, because it was in the quadrant 1 position, where the quadrant was a very favorable situation. Keywords: SWOT Analysis, Marketing Strategy, MSMEs